Human rights transformation in practice - Destrooper, Tine; Merry, Sally Engle, 1944-2020 (Pennsylvania studies in human rights., 2018)
Human rights are increasingly described as being in crisis, but the ideals inherent in them remain appealing. Human Rights Transformation in Practice demonstrates how these ideals are embedded in everyday social practice and activism, and how they can be reinterpreted and redefined in a variety of contexts and for a range of problems.